Valor liberdade do trabalhador e o trabalho análogo ao de escravo - Aguiar, Wesley Henrique de Mello (2020)
The study approaches the workers‘ value of freedom and its violation, by submitting them to conditions analogous to that of a slave. The historical aspects of freedom at work have been analyzed, as well as the prospects for the value of work in political and economic thinking, in which, have contributed to protecting the workers‘ value of freedom. Both mainstream International Norms and the Brazilian Constitutional Rules have been studied, which guarantee minimum human and fundamental rights in the protection of the workers, and their individual and collective freedoms. Work conditions have been investigated, that are performed individually or cumulatively, featuring conditions analogous to that of a slave, according to Article 149 of the Brazilian Penal Code, as well as how these work conditions violate workers‘ values of freedom. The mechanisms of the Brazilian legal system and its importance in fighting all forms of slave-like work have been analyzed, aiming to protect these freedoms. The study has been developed following a deductive method, with a qualitative approach by the procedure of descriptive observation on a doctrinal and jurisprudential basis.